Ex vivo torsional properties of the Targon Vet Nail System in canine femurs: comparison with the 2.4 mm LC-DCP Plate - Macedo, Aline Schafrum [UNESP] (2015)
The purpose of this study was to evaluate the torsional stability of the Targon® Vet Nail System (TVS) in small canine femurs and to study the effect of different bolt locations on the torsional strength of the constructs compared to 2.4 mm Low Contact - Dynamic Compression Plates (LC-DCP®). Thirty-six femurs were harvested from fresh small dog cadavers and allocated to 3 groups (n=12) ensuring equal bone length distribution between groups. In all bones, points 1 mm below the lesser trochanter and 1 mm above the fabellae were marked and a transverse osteotomy was performed in the middle. In group 1, the bone was fixed with the 2.5 mm TVS with the bolts applied at those pre-identified marks, leaving a 2 mm gap between fragments. In group 2, the TVS was also used but the proximal bolt was placed in a location equidistant between the proximal mark and the osteotomy, resulting in a 25% shorter inter-bolt distance. In group 3, 7-hole 2.4 mm LC-DCP® plates were applied to the lateral aspect of the bones. All constructs were tested non-destructively at a rate of 1°/sec under load control between a torque of plus and minus 0.57 Nm for 10 cycles. Cyclic loading was followed by an acute torsion to failure. The last of the 10 cycles was used to measure the deformation under non-destructive load. The stiffness and torque to failure of the constructs were measured from the final torque-deformation curves. Yield point was defined as a 1° deformation beyond the expected linear behavior of the constructs. All results were tested for normality and compared using ANOVA and Tukey post hoc tests. P values < 0.05 were considered significant. Torque at yield was 0.806 +/- 0.183 and 0.805 +/- 0.093 Nm for groups 1 and 2 and 1.737 +/- 0.461 Nm for group 3. Stiffness was 0.05 +/- 0.01; 0.05 +/- 0.007 and 0.14 +/- 0.015 Nm/° for groups 1 to 3 respectively. Displacement under cyclic loading was 16.6° +/- 2.5°; 15.6° +/- 2.1° and ...